Determination of Adoption of Children in Judicial Settings in Religious Courts and District Courts Batusangkar - Indriani, Dewi; Cosr, Rey; Deg , Alex; Arngo, Lawr (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
The main problem in this study is how to Determine Child Adoption in the Judicial Environment in the Religious Court and the Batusangkar District Court. The problem studied is about the factors and allusions of child adoption between Indonesian citizens who are Muslims and the positive and negative impacts of child adoption at the Religious Court and the Batusangkar District Court. The purpose of this study is to explain the factors affecting the adoption of children in the Religious Court and the Batusangkar District Court and explain the positive and negative impacts of the adoption of the child. Based on the research conducted by the author, the author concludes that the factors that influence the adoption of children both in the Religious Court and in the Batusangkar District Court include helping the education and future of the adopted child, because the adoptive parents do not have children, as one of the ways or solutions for husband and wife who have been married for a long time but have not been blessed with children, to help his underprivileged brother, in addition,/income allowance.